Models of sequential decision making in consumer lending - Kanshukan Rajaratnam; Peter A. Beling; George A. Overstreet (Decision Analytics, 2016)
In this paper, we introduce models of sequential decision making in consumer lending. From the definition of adverse selection in static lending models, we show that homogenous borrowers take-up offers at different instances of time when faced with a sequence of loan offers. We postulate that bounded rationality and diverse decision heuristics used by consumers drive the decisions they make about credit offers. Under that postulate, we show how observation of early decisions in a sequence can be informative about later decisions and can, when coupled with a type of adverse selection, also inform credit risk. We show through two examples how lenders may use such information in setting their offer rates.
Keywords: 330; Sequential decision making; Consumer loans; Credit risk